EFFECT OF PROJECT-BASED LEARNING IMPLEMENTATION ON XI-GRADE CULINARY STUDENTS’ PERFORMANCE IN CUCUR CAKE PRODUCTION AT SMKN 6 SURABAYA - Filothei Manalu; Yunus Karyanto (JF Publisher, 2025)
This research investigates the influence exerted by the application of the Project-Based Learning (PjBL) strategy on students’ academic performance in practical culinary education, specifically in the preparation of kue cucur among Grade XI students in the culinary arts program at SMKN 6 Surabaya. Initial observations indicated low performance due to weaknesses in technical skills, raw material management, and innovation in presentation. Traditional instructional methods were found inadequate for developing the practical competencies and creativity demanded by the culinary industry. This research adopts a quantitative method within a quasi-experimental framework. Two classes were purposively selected: an experimental group taught through the Project-Based Learning (PjBL) model and a control group instructed using conventional methods. Data were obtained through pre-tests and post-tests, then analyzed to assess normality and homogeneity of variance. An Independent Samples T-test was subsequently conducted using SPSS version 27. The analysis revealed a statistically significant difference between the two groups, with a p-value of 0.001 (p < 0.05) .Students in the experimental group exhibited greater improvements in theoretical understanding, practical execution, and creativity in product presentation. These findings suggest that the PjBL model effectively enhances both cognitive and practical competencies in vocational culinary education and provides a more engaging and industry-relevant learning experience.